Bacillus subtilis is crucial for the normal growth of mycelium for Stropharia rugosoannulata - Yu Tian; Man Cui; Suyue Zheng; Nuolin Yang; Qinghao Fan; Jinwei Zhang; Gaige Shao; Ruiying Zhang (Fungal Biology, 2026)

Selective flotation separation of spodumene from silicate gangue enhanced by ultrasound-induced interfacial dissolution - Dongfang Lu; Man Cui; Lanlan Chen; Jinrui Cheng; Mingzhu Zhang; Yuhua Wang; Xiayu Zheng (Minerals Engineering, 2026)

Mycorrhizal associations influence the origin and stability of topsoil organic carbon fractions: implications for subtropical forest restoration - Yongmeng Jiang; Maokui Lyu; Haohao Su; Yuming Lu; Cui Deng; Jueling Liu; Man Wang; Weisheng Lin; Jinsheng Xie (Forest Ecology and Management, 2026)

A synergistic probiotic delivery strategy: Pectin-protein-hyaluronic acid hydrogel microcapsules enhance the protective efficacy of Lacticaseibacillus rhamnosus JY027 against DSS-induced colitis - Yue Meng; Fangfang Su; Yuhan Cui; Hanying Yang; Qian Guo; Wei Zhang; Ling Guo; Yujun Jiang; Chaoxin Man; Yu Zhang (Food Bioscience, 2026)

Full mechanical response prediction for staged prestressed composite beams driven by a hybrid GRU-VAE and BiLSTM framework - Zexuan Sun; Tianxia Cui; Man Xu; Bin Zeng; Chun-Lin Wang (Engineering Structures, 2026)

Deciphering energy storage mechanism of oxygen-deficient mesoporous MnO2 for aqueous zinc-ion batteries: Operando and ex-situ analysis - Hansol Kim; Chenglin Cui; Yelim Kwon; Soowon Choi; Sujin Lee; Sangbin Park; Won-Sub Yoon; Ravindra N. Bulakhe; Ji Man Kim (Chemical Engineering Journal, 2026)

Reduced nerve growth factor (NGF) mediates arsenic-induced mitochondrial dynamics imbalance and neuronal damage both in vivo and in vitro - Xinbo Ma; Liu Yang; Xinhua Shao; Jia Cui; Ziqiao Guan; Man Lyu; Shuaifei Yang; Na Fang; Yang Liu; Yanhui Gao; Xiaona Liu; Yanmei Yang (Journal of Zhejiang University-SCIENCE B, 2026)

Selective flotation separation of spodumene and feldspar under low alkalinity enabled by a sulfonate-based organic depressant - Man Cui; Dongfang Lu; Yuhua Wang; Xiayu Zheng (Minerals Engineering, 2026)

Spatial engineering of adjacent pair single-atom catalyst for reaction-pathway decoupling in advanced oxidation - Man Yang; Yongquan Zhu; Jing Mei; Haibo Li; Wengang Liu; Jing Lu; Jie Cui; Shaodong Sun; Yang Song; Xinyang Liu; Yujing Ren (Journal of Hazardous Materials, 2026)

Fe(III)-mediated interfacial regulation of a sulfonate-based depressant for selective flotation of spodumene from quartz under low-alkaline conditions - Man Cui; Dongfang Lu; Yuhua Wang; Xiayu Zheng (Journal of Environmental Chemical Engineering, 2026)

Priority control of potentially toxic elements in urban park soils through integrated source apportionment and health risk assessment - Xiangtian Man; Jian Sun; Xingnian Ren; Mengli Chen; Cheng Yang; Ruxin Yang; Ailian Li; Junfang Cui; Han Zhang (Environmental Geochemistry and Health, 2026)

Seismic resilience assessment of pile-supported wharves in liquefiable sites considering recovery path diversity and failure probability - Xiaoyu Zhang; Mingchu Yang; Hai Liu; Xiaofeng Man; Jindong Yang; Jie Cui (Engineering Structures, 2026)

Functional complementarity of abundant and rare taxa mediates soil carbon sequestration during subtropical forest restoration - Yuming Lu; Maokui Lyu; Yongmeng Jiang; Cui Deng; Jueling Liu; Man Wang; Weisheng Lin; Jinsheng Xie (Journal of Environmental Management, 2026)

Ecological lock-in and functional mismatch in abandoned coastal ponds: mechanisms and management implications - Yi'na Li; Yanzi Cai; Junjun Bai; Ying Man; Dongxue Li; Qing Wang; Yujia Zhai; Ping Qi; Tian Xie; Baoshan Cui (Journal of Environmental Management, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Seasonal shifts in phytoplankton community assembly mediated by hydrological connectivity in a sluice-regulated distributary estuarine network—as a case in the Pearl River Estuary - Yanzi Cai; Xia Li; Guogui Chen; Yiliang Xie; Yujia Zhai; Tian Xie; Mingyu Wang; Fang Gao; Meili Feng; Ying Man; Baoshan Cui (Journal of Hydrology, 2026)

Laser-induced graphene in-situ embedded with high-entropy alloys from tea polyphenol/cellulose nanofiber film for solar-driven interfacial evaporation - Man Liu; Jiashu Song; Peilong Zhao; Luxue Cui; Xiaofei Mao; Mingyang Liu; Nan Zhao; Minjian Yang; Jingqing Gao (Chemical Engineering Journal, 2026)

Dual-source-driven snowman-shaped PMO@MnO2@C@DMSN-SS31 Janus nanomotors for enhanced deep penetration and restoration of mitochondrial function to modulate the inflammatory microenvironment for cartilage repair - Xiaolei Zhang; Zhihan An; Yichen Zhang; Jinquan Cui; Qiang He; Chuandong Cai; Jianing Liu; Zhentao Man; Wei Li (Chemical Engineering Journal, 2026)

Gender-specific association between PM2.5 exposure and cognitive function in middle-aged and elderly chinese: Evidence from CHARLS - Man Quan; Jing Cui; Yukui Chen; Jiayi Hao; Chenshu Ge; Xiaomei Li; Juan Wang; Duolao Wang; Leilei Pei; Yijun Kang; Lu Ye (Air Quality, Atmosphere & Health, 2026)

Introducing tree species of Schima superba and Liquidambar formosana enhances soil carbon sequestration by alleviating microbial phosphorus limitation and modulating microbial metabolism in degraded pine forests - Shuqi Shen; Jueling Liu; Yongmeng Jiang; Yuming Lu; Cui Deng; Man Wang; Jinsheng Xie (Pedobiologia, 2026)

Reverse temporal spectral signal extraction and deep spectral signal decoupling fusion for detection of SCLB infection process - Guohui Liu; Jinyang Chao; Changle Guo; Lulu An; Yang Liu; Hong Sun; Chunqi Zhang; Mingjia Liu; Zheng Cui; Man Zhang; Minzan Li; Wei Yang (Computers and Electronics in Agriculture, 2026)

Molecular insights into the temperature-responsive interfacial properties of sodium oleate–based combined collectors for spodumene flotation - Ying Zhang; Yuhua Wang; Ning Sun; Man Cui (Minerals Engineering, 2026)

Fluorescent molecular rotor-based probes for sensitive and selective detection of nanoplastics in food, environment, and living cells - Man Du; Shuang Hou; Haohua Jiang; Yue Zhang; Haijun Lv; Bin Cui; Hongxia Du; Chen Shen; Peng Wang (Food Chemistry, 2026)

Ion-mediated interfacial water reconstruction in cellulose-biochar aerogels enables seawater evaporation faster than pure water - Man Yuan; Lei Yang; Wei Liu; Meng Hu; Cheng Zhou; Xiaobei Guo; Sheng Cui (Chemical Engineering Journal, 2026)

Construction and temporal external validation of interpretable machine-learning models for predicting tigecycline-associated hypofibrinogenemia - An Fu; Daihong Guo; Man Zhu; Le Cai; Ao Gao; Liqiang Cui (European Journal of Clinical Pharmacology, 2026)

Comparative structural and functional characterization of Chlamydomonas reinhardtii proteins extracted by alkaline and ultrasound-assisted enzymatic methods - Man Zhou; Wenxin Liu; Ruixian Chen; Jie Yu; Yushuang Ma; Anjun Chen; Hejun Wu; Shutao Yin; Qiang Cui (Food Hydrocolloids, 2025)

Smart textiles: Sustainable, self-powered, portable, and durable wearable textiles for human health monitoring - Man Zhou; Jia Wu; Liang Huang; Miao Miao; Yifan Cui; Xinyang He (Chemical Engineering Journal, 2025)

Assessment of flood risk in jinsha river basin based on land use value and PSR model - Xiao Chen; Ran Zhai; Wen Fang; Liwen Xu; Lili Liang; Juanru Yang; Hanlin Man; Zhenyu Lv; Chao Wang; Deng Liu; Mengqing Cui (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Deriving nickel carbides from Ni-MOFs to boost CO selectivity in CO2 hydrogenation - Xiaorui Wang; Guiming Xie; Chaonan Cui; Yi Man; Zhou-jun Wang (Fuel, 2025)

Amino acid promotes the formation of enals and 1-octen-3-ol from linoleic acid during the thermal reaction between alanine-xylose Amadori compound and Agrocybe aegerita enzymatic hydrolysates - Tong Zhou; Qingqing Chai; Man Zhang; Heping Cui; Mingzhou Song; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2025)

Hydrogen production from supercritical water gasification of corn stalk with reactive co-solvents: Regulator roles of free radicals - Da Cui; Xuelong Sui; Yuqi Wang; Hon Man Luk; Shuang Wu; Chunlei Wu; Jinghui Zhang; Qiuyun Lu; Qing Wang; Xuehua Zhang (Chemical Engineering Journal, 2025)

Recent advances in non-precious metal electrocatalysts for anion exchange membrane water electrolysis: Mechanistic insights, catalyst design, and structural regulation strategies - Qing Wang; Yuan Wang; Hon Man Luk; Jihui Tang; Shuang Wu; Dongyang Wu; Zhongyuan Hu; Da Cui; Jinghui Zhang (Chemical Engineering Journal, 2025)

Effect of oleic acid iodine value on the flotation performance of oleic acid-based collectors for spodumene - Ying Zhang; Ning Sun; Yuhua Wang; Liu Luo; Man Cui; Yu Li (Journal of Environmental Chemical Engineering, 2025)

Dual-functional GO composite aerogels for water purification and desalination via heavy metal adsorption and solar evaporation - Man Yuan; Lei Yang; Zihan Wang; Jiangping Du; Sisi Shang; Wei Liu; Meng Hu; Sheng Cui (Desalination, 2025)

Excellent durability and multifunctional textiles with dual-mode evaporative and radiative cooling enabled by in-situ growth of SiO2 and electrostatic network coating - Luxuan Zhang; Bo Xu; Man Zhou; Ying Liu; Ying Zhang; Li Cui; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

Dual-functional nanocellulose/graphene aerogel for enhanced solar interfacial water evaporation and per−/polyfluoroalkyl substances removal - Jiashu Song; Peilong Zhao; Xiaofei Mao; Luxue Cui; Man Liu; Nan Zhao; Guofeng Shen (Chemical Engineering Journal, 2025)

Cement aerogel building envelopes: achieving building energy efficiency and acoustic noise reduction - Zihao Song; Haoran Ma; Man Yuan; Sisi Shang; Wei Liu; Sam Sukgoo Yoon; Sheng Cui (Chemical Engineering Journal, 2025)

Identifying novel modifiable risk factors for ischemic stroke through phenome-wide association study and Mendelian randomization analyses in a large-scale prospective cohort - Siyu Wu; Jialin Li; Xinyue Zhao; Jincheng Li; Shuaizhou Chen; Chengtong Zhang; Chen Suo; Yingzhe Wang; Xingdong Chen; Mei Cui; Qiuhong Man; Yanfeng Jiang (GeroScience, 2025)

Programming BioZ, a promiscuous enzyme in bacterial biotin synthesis - Yongchang Xu; Shuyu Zhou; Tao Cui; Jiuxin Qu; Huimin Zhang; Man Huang; Youjun Feng (Science Bulletin, 2025)

Impact of cationic reagent structure on the performance of combined collectors in spodumene-feldspar flotation system - Ying Zhang; Yuhua Wang; Ning Sun; Haiqiang Feng; Yu Li; Man Cui (Minerals Engineering, 2025)

Temperature effects on sodium oleate flotation performance and interfacial interactions in spodumene flotation - Ying Zhang; Yuhua Wang; Ning Sun; Man Cui (Journal of Water Process Engineering, 2025)

Role of exogenous xylose during its co-heating with alanine-xylose Amadori compound: Competitively promoting 2-furfural formation and limiting pyrazines generation - Tong Zhou; Qingqing Chai; Man Zhang; Heping Cui; Ahmad Mohammad; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2025)

Exploring motor unit and neuromuscular junction dysfunction in aging and sarcopenia: insights from electromyography in systematic review - Can Cui; Yong Hu; Ronald Man Yeung Wong; Ning Zhang; Yuzhou Guan; Wing-hoi Cheung (GeroScience, 2025)

Assessment of in vitro digestion properties and prebiotic potential of chayote (Sechium edule) pectin - Qing Guo; Xiaoxue Wang; Chun Yang; Jie Yu; Qiang Cui; Xiaoyan Hou; Guanghui Shen; Man Zhou; Hong Liu; Anjun Chen; Zhiqing Zhang (Food Bioscience, 2025)

Iodine crystallization-promoted efficient capture of iodine by nonporous covalent organic polymer - Yong Man; Xiaoshuang Cui; Ruobing Wang; Shiqi Chai; Chenchen Song; Yaming Sun; Renyong Zhao; Lijun He (Journal of Hazardous Materials, 2025)

Comprehensive mechanisms of epigallocatechin-3-gallate (EGCG) metabolism during tea dieback disease infection in tea plant (Camellia sinensis) - Yiyong Chen; Bo Zhou; Jianlong Li; Man Zhang; Yingying Cui; Jinchi Tang (Food Bioscience, 2025)

Biomass aerogel: An emerging eco-friendly material for adsorbing pollutants in water - Wei Liu; Chen Dai; Linheng He; Xingyu Liu; Zhiyang Zhao; Wenqian Yan; Man Yuan; Zihao Song; Sheng Cui (Chemical Engineering Journal, 2025)

The assessment of environmental effect and economic benefit for apple orchard under different stand ages in the Loess Plateau, China - Man Zhang; Lu Cai; Cui Li; Qiong Zhang; Weixin Wang; Kaixuan Wang (Plant and Soil, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

Extraction and immobilization of potato esterase and its application in the detection of potato glycoalkaloids - Qing Guo; Jing Li; Jie Yu; Qiang Cui; Xiaoyan Hou; Hong Liu; Man Zhou; Guanghui Shen; Zhiqing Zhang (Food Bioscience, 2025)

Structure-phase transformation of bismuth oxide to BiOCl/Bi24O31Cl10 shoulder-by-shoulder heterojunctions for efficient photocatalytic removal of antibiotic - Man Yang; Zhenzhen Shi; Shaodong Sun; Bian Yang; Jie Cui; Jianing Li; Daqin Yun; Nian Lei (Journal of Environmental Sciences, 2025)

Homestead withdrawal behaviour of rural migrants in China: The role of joint reform of hukou system and homestead system - Xiao Cui; Eddie Chi Man Hui; Jianfu Shen; Xin Lin; Siyi Wang; Fang He (Journal of Rural Studies, 2025)

Insights into selectivity modulation for CO2 hydrogenation over Na-NiLa(BDC) catalysts: The role of frustrated Lewis pairs - Xiaorui Wang; Yi Man; Runduo Zhang; Chaonan Cui; Kangzhou Wang; Zhou-jun Wang (Chemical Engineering Journal, 2025)

Can cadmium-contaminated rice be used to produce food additive sodium erythorbate? - Lei Sun; Xiaoju Zhang; Yanzheng Zhou; Zhen Peng; Fengjie Cui; Qiang Zhou; Zaiwei Man; Jing Guo; Wenjing Sun (Food Chemistry, 2025)

Lactobacillus paracasei JY062 with its exopolysaccharide ameliorates intestinal inflammation on DSS-induced experimental colitis through TLR4/MyD88/NF-κB signaling pathway - Yue Su; Zhengying Cui; Chen Chen; Xinyan Yang; Yujun Jiang; Wei Zhang; Yu Zhang; Chaoxin Man (Food Bioscience, 2025)

A tetrahedral DNA nanoplatform with ultrasound-triggered biomimetic nanocarriers for targeted siMCM2 delivery and reversal of imatinib resistance in gastrointestinal stromal tumors - Li Han; Quan Dai; Chuanshi He; Jinshun Xu; Likun Cui; Xiaoxiao Xie; Zijian Zhang; Min Zhuang; Xiangyu Li; Man Lu (Chemical Engineering Journal, 2025)

Electro-Fenton purification of floodwater with a poly(vinyl alcohol)-treated FeNi3@laser-induced 3D-graphene composite anode from Kraft paper - Nan Zhao; Jingshen Zhang; Fengmei Cao; Peilong Zhao; Xiaofei Mao; Jiashu Song; Luxue Cui; Man Liu; Xiaoyu Huang; Yuening Zhang; Weimin Zhang; Yuguang Zhou; et al. (Chemical Engineering Journal, 2025)

Lactobacillus paracasei JY062 and its exopolysaccharide enhance the intestinal barrier through macrophage polarization and Th17/Treg cell balance - Yue Su; Zhengying Cui; Xinyan Yang; Yujun Jiang; Wei Zhang; Yu Zhang; Chaoxin Man (Food Research International, 2024)

Salmon origin traceability based on hyperspectral imaging data fusion strategy and improved deep learning method - Zhiyong Zou; Dongyu Yuan; Qingsong Wu; Qianlong Wang; Menghua Li; Jiangbo Zhen; Chong Xu; Shutao Yin; Qiang Cui; Man Zhou; Lijia Xu (Food Control, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

High-quality litter exerts a greater effect on soil carbon gain in unrestored than restored pine plantations - Shiting Li; Yongmeng Jiang; Maokui Lyu; Cui Deng; Wei Deng; Man Wang; Jueling Liu; Yuming Lu; Jinsheng Xie (Science of The Total Environment, 2024)

Biochar amendment alleviates soil microbial nitrogen and phosphorus limitation and increases soil heterotrophic respiration under long-term nitrogen input in a subtropical forest - Quan Li; Hangxiang Ji; Chao Zhang; Yongxing Cui; Changhui Peng; Scott X. Chang; Tingting Cao; Man Shi; Yongfu Li; Xiao Wang; Junbo Zhang; Xinzhang Song (Science of The Total Environment, 2024)

Responses of greenhouse gas emissions to increased precipitation events in different ecosystems: A meta-analysis - Cui Li; Weixin Wang; Kaixuan Wang; Yuesheng Wang; Man Zhang (CATENA, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Primary and oxidative source analyses of consumed VOCs in the atmosphere - Yaqi Cui; Baoshuang Liu; Yufeng Yang; Sicong Kang; Fuquan Wang; Man Xu; Wei Wang; Yinchang Feng; Philip K. Hopke (Journal of Hazardous Materials, 2024)

Combined role of stearic acid and maleic anhydride in the development of thermoplastic starch-based materials with ultrahigh ductility and durability - Sixian Peng; Guanghui Cui; Jianfeng Li; Fangyi Li; Maocheng Ji; Chuanwei Zhang; Tianshuo Meng; Jianyong Li; Jia Man (Carbohydrate Polymers, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Natural polysaccharide-dominated synthesis of MnO2 nanoparticles as textile coating for efficiently removing indoor bacteria and air pollutants - Xueming Bao; Yun Yuan; Zirong Li; Yuanyuan Yu; Li Cui; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Soil amendments reduce CH4 and CO2 but increase N2O and NH3 emissions in saline-alkali paddy fields - Hu Cui; Hui Zhu; Fu-Man Zhang; Xin-Yi Wang; Sheng-Nan Hou; Wei-Dong Feng (Science of The Total Environment, 2024)

Self-cleaning, energy-saving aerogel composites possessed sandwich structure: Improving indoor comfort with excellent thermal insulation and acoustic performance - Zihao Song; Lei Su; Man Yuan; Sisi Shang; Sheng Cui (Energy and Buildings, 2024)

A framework to quantitatively assess the influence of land use and land cover on coastal wetland hydrological connectivity from a landscape resistance perspective - Ying Man; Jizeng Du; Zhongmin Lian; Qing Wang; Baoshan Cui (Science of The Total Environment, 2024)

A natural mutant kumquat fruit with abnormal oil glands shows lower volatile production, better fruit flavor and higher resistance to postharvest disease - Man Zhu; Yang Wang; Zhebin Zeng; Xi Wu; Jiacheng Teng; Jingzong Zhang; Qianrong Han; Qiaoli Ma; Chuanwu Chen; Yunjiang Cheng; Xiuxin Deng; Niels J. Nieuwenhuizen; et al. (Postharvest Biology and Technology, 2024)

Novel ternary deep eutectic solvent for highly efficient dissolution of lignins: Dissolution behavior and mechanism study - Man Zhang; Bingyan An; Kejing Wu; Jinming Zhang; Jinfeng Wang; Qingtao Liu; Yongming Cui; Houfang Lu (Journal of Cleaner Production, 2024)

Testate amoebae (Protozoa) in lakes of the Qinghai-Tibet Plateau: Biodiversity, community structures, and protozoic biosilicification in relation to environmental properties and climate warming - Yangmin Qin; Anatoly Bobrov; Daniel Puppe; Hui Li; Baiying Man; Jing Gong; Jie Wang; Yongde Cui; Yansheng Gu; Ulrike Herzschuh; Shucheng Xie (Science of The Total Environment, 2024)

Natural deep eutectic solvent: A novel and green mordant for the natural dye - Zhe Jiang; Guolin Zheng; Yifan Cui; Wenda Wang; Xianqin Shang; Yimin Wei; Man Zhou; Ping Wang; Yuanyuan Yu; Qiang Wang (Chemical Engineering Journal, 2024)

Piperlongumine inhibits esophageal squamous cell carcinoma in vitro and in vivo by triggering NRF2/ROS/TXNIP/NLRP3-dependent pyroptosis - Yue Cui; Xiao-bo Chen; Ying Liu; Qian Wang; Jie Tang; Man-jun Chen (Chemico-Biological Interactions, 2024)

Study on the infection control performance under interactive cascade ventilation: A focus on a conference room environment - Han Li; Qiuyue Cui; Xiangfei Kong; Man Fan (Building and Environment, 2024)

Comparative study on the thermal characteristics under different air distribution strategies oriented to non-uniform environment: An indoor experiment - Han Li; Qiuyue Cui; Xiangfei Kong; Man Fan (Building and Environment, 2023)

Three new triterpenoid glycosides from Aronia melanocarpa (Michx.) Elliott - Ting-Ting Guo; Man-Li Zhang; Zhao-Cui Sun; Li-Mei Zhang; Xu-Dong Xu; Bi-Huang Hu (Natural Product Research, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

A multilevel social-ecological network approach for reconciling coastal saltmarsh conservation and development - Ying Man; Kang Liu; Tian Xie; Fangwen Zhou; Wei Shi; Zezheng Liu; Qing Wang; Baoshan Cui (Journal of Environmental Management, 2023)

Near-infrared light-enhanced enzymatic activity of laccase-platinum nanoparticles as a biosensor for colorimetric and visible detection of ascorbic acid - Guolin Zheng; Zhe Jiang; Yifan Cui; Man Zhou; Yuanyuan Yu; Ping Wang; Qiang Wang (Chemical Engineering Journal, 2023)

The disruption of blood-brain barrier induced by long-term arsenic exposure is associated with the increase of MMP-9 and MMP-2: The characteristics are similar to those caused by senescence - Man Lv; Xinbo Ma; Kunyu Zhang; Meichen Zhang; Yi Ji; Lin Cheng; Xinhua Shao; Ziqiao Guan; Jia Cui; Yanhui Gao; Yang Liu; Yanmei Yang; et al. (Chemico-Biological Interactions, 2023)

Effects of microplastics and tetracycline on intestinal injury in mice - Lixin Wang; Jiamin Chen; Xuan Zhang; Man Xu; Xuyan Zhang; Wanqing Zhao; Jiansheng Cui (Chemosphere, 2023)

Implication of ferroptosis in hepatic toxicity upon single or combined exposure to polystyrene microplastics and cadmium - Lixin Wang; Xuan Zhang; Man Xu; Guangzhe Zheng; Jiamin Chen; Shan Li; Jiansheng Cui; Shuping Zhang (Environmental Pollution, 2023)

Superhydrophobic, photothermal, and UV-resistant coatings obtained by polydimethylsiloxane treating self-healing hydrophobic chitosan-tannic acid surface for oil/water separation - Guolin Zheng; Yifan Cui; Zhe Jiang; Man Zhou; Yuanyuan Yu; Ping Wang; Qiang Wang (Chemical Engineering Journal, 2023)

Whole-genome analyses reveal the genomic diversity and selection signatures of Hainan cattle - Si Chen; Chencheng Chang; Ke Cui; Weijie Yang; Boling Li; Shiheng Ni; Wencan Zhang; Shiyuan Li; Xubo Li; Guansheng Wu; Lianbin Li; Qiaoling Chen; et al. (Livestock Science, 2023)

Numerical simulation on the impact characteristics between rockfalls of different shapes and gravel cushions - Chun Zhu; Jia-jun Xu; Ya-jun Wang; Man-chao He; Sheng-hua Cui; Xiao-hu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2023)

In-situ elemental quantitative imaging in plant leaves by LA-ICP-MS with matrix-matching external calibration - Zewei Cui; Man He; Beibei Chen; Bin Hu (Analytica Chimica Acta, 2023)

The composition characteristics of endophytic communities and their relationship with metabolites profile in Ephedra sinica under wild and cultivated conditions - Hui Zhang; Ye Xia; Jin-Long Cui; Xin Ji; Shuang-Man Miao; Gang Zhang; Yi-Min Li (Environmental Science and Pollution Research, 2023)

A novel mussel-inspired layered montmorillonite-based composite aerogel for high-efficiency removal of heavy metal ions - Man Yuan; Xin Ye; Zihao Song; Limin Che; Sisi Shang; Meiyu Yuan; Shucai Wu; Dongsheng Liu; Sheng Cui (Journal of Water Process Engineering, 2023)

Guanidinylated/PEGylated chitosan in the bioink promotes the formation of multi-layered keratinocytes in a human skin equivalent - Meng Zhu; Tian Hu; Wei Song; Xiaoliang Cui; Ye Tian; Bin Yao; Man Wu; Sha Huang; Zhongwei Niu (Carbohydrate Polymers, 2023)

A photothermal cellulose-based material for rapid anti-bacteria and HCHO removal via sequential formation of MnO2 coatings and amine-quinone networks - Xueming Bao; Leilei Wu; Yuanyuan Yu; Bo Xu; Li Cui; Man Zhou; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2023)

Peptide profiles and allergy-reactivity of extensive hydrolysates of milk protein - Qiang Cui; Zhiqing Zhang; Meiliang Li; Man Zhou; Xiaomeng Sun (Food Chemistry, 2023)

Terpenoids of quinoa bran suppresses colorectal cancer by inducing cell apoptosis - Man Ding; Xuechen Zhang; Jiangying Shi; Kaili Cui; Ruipeng Yang; Fengming Liu; Shuhua Shan; Ghani Israr; Zhuoyu Li (Food Bioscience, 2023)

Quantitative evaluation of sea reclamation activities on tidal creek connectivity - Ying Man; Fangwen Zhou; Qing Wang; Baoshan Cui (Frontiers in Marine Science, 2023)
Deltas are in a dynamic balance due to the impact of fluvial and coastal flooding, and hydrological connectivity plays an important role. In recent decades, the dynamic equilibrium has been influenced by upstream and local human activities, including sea reclamation activities. However, in most instances, the influence of human activities has not been explicitly distinguished and quantified in detail. In this paper, the influence of sea reclamation activities on hydrological connectivity in the Yellow River Delta was quantified by parameterizing the resistance surfaces (a spatial layer that assigns a value to each landscape feature, indicating the degree to which that variable impedes or promotes movement) that includes sea reclamation activities. By optimizing a functional relationship between landscape features and hydrological connectivity (water flow movement patterns), the values in the resistance surfaces could be assigned. We first calculated hydrological distances among bifurcations from 1985 to 2020 with a 5-year interval representing the hydrological connectivity of each tidal creek. The sea reclamation activities in the YRD were classified into four: reclaimed land, sea enclosure activity, freshwater resource facilities, and engineering in the oil field to create resistance surfaces. We identified that the periods of 1990–1995 and 2000–2005 were under the most severe influence of sea reclamation activities. Sea enclosure activity, freshwater resource facilities, and engineering in oil fields played major roles in composing resistance surfaces. Mariculture (quantified relative resistance value, 1.00), reservoir (0.92), agriculture (0.91), and river (0.97) were the features with the highest resistance values in the initial and mature development stages. The formation of resistance (costs to movement) was due to human activities and natural factors, for example, the evolution of tidal creeks. To develop the resource in tidal flats sustainably, systematic monitoring and sufficient conservation awareness were required. This study contributed to coastal management and planning by providing a quantified assessment of different types of sea reclamation activities.

Toxicity mechanism of peri-implantation pesticide beta-cypermethrin exposure on endometrial remodeling in early pregnant mice - Yong-Jiang Zhou; Qian-Feng Qiao; Li-Qing Wang; Tao-Yu Sheng; Man-Xue Cui; Qi-Duo Chen; Can-Yang Wang; Yun-Xiao Zhang (Toxicology, 2023)

STCANet: Spatiotemporal Coupled Attention Network for Ocean Surface Current Prediction - Cui Xie; Ping Chen; Tenghao Man; Junyu Dong (Journal of Ocean University of China, 2023)

circTAB2 inhibits lung cancer proliferation, migration and invasion by sponging miR-3142 to upregulate GLIS2 - Weiling Man; Yumeng Cui; Jie Li; Yanghua Li; Jie Jin; Yang Jin; Xiaojie Wu; Rongbin Zhong; Xiang Li; He Yao; Yanli Lin; Lihe Jiang; et al. (Apoptosis, 2023)

Exploring the apparent properties and Q-markers for quality control of Cornus officinalis - Yu Liu; Yingfang Cui; Xv Liang; Shuli Man; Xia Li; Lorenzo Pecoraro; Giuseppe Venturella; Wenyuan Gao (Food Chemistry, 2023)

Fabrication of In–S-co-doped two-dimensional BiOCl coupling with surface hydroxylation toward simultaneously efficient charge separation and redox capability for photocatalytic water remediation - Tingfang Xie; Shaodong Sun; Yu Guo; Yongguang Luo; Man Yang; Bian Yang; Jie Cui (Chemosphere, 2023)

Application and research progress of infrared thermography in temperature measurement of livestock and poultry animals: A review - Zhenjiang Cai; Jialiang Cui; Hongbo Yuan; Man Cheng (Computers and Electronics in Agriculture, 2023)

A strategy to promote the ORR electrocatalytic activity by the novel engineering bunched three-dimensional Pd-Cu alloy aerogel - Xiaodong Wu; Chunsheng Ni; Jianwei Man; Xiaodong Shen; Sheng Cui; Xiangbao Chen (Chemical Engineering Journal, 2023)

PWPNet: A Deep Learning Framework for Real-Time Prediction of Significant Wave Height Distribution in a Port - Cui Xie; Xiudong Liu; Tenghao Man; Tianbao Xie; Junyu Dong; Xiaozhou Ma; Yang Zhao; Guohai Dong (Journal of Marine Science and Engineering, 2022)
In this paper, a 2-stage cascaded deep learning framework, Port Wave Prediction Network (PWPNet), is proposed for real-time prediction of significant wave height (SWH) distribution in a port. The PWP-out model of the first stage, predicting port-entrance wave parameters, utilizes three branches, the first branch using a Long Short Term Memory (LSTM) module to learn the temporal dependencies of time sequences of port-entrance wave parameters, the second branch using Wave and Wind field Feature Extraction (WWFE) modules, composed of a residual network with spatial and channel attention, to capture spatiotemporal characteristics of outside-port 2D wave and wind field data, the third branch using multi-scale time encoding to capture the periodic characteristics of waves and wind. The PWP-in model of the second stage, estimating the in-port SWH distribution, uses port-entrance wave parameters based on a customized Artificial Neural Network (ANN) and takes PWP-out’s output as its input. A comparison of the performance of PWP-out and mainstream machine learning models including LSTM, GRU, BPNN, SVR, ELM, and RF at Hambantota Port shows that PWP-out outperforms all other models regarding medium-term (25–48 h), med–long-term (49–72 h), and long-term (73–96 h) predictions, and ablation experiments proved the effectiveness of the three branches. Furthermore, the performance comparison of our PWPNet and other 2-stage models of LSTM, GRU, BPNN, SVR, ELM, and RF cascaded with PWP-in shows that PWPNet outperforms those cascaded models for medium-term to long-term predictions of SWH distribution in a port.

Quantitative analysis of lake-cooling effect in Hefei City, China, based on multispectral remote sensing and its response to urban expansion - Xuening Lin; Yuhuan Cui; Shuang Hao; Hong Hong; Man Zhang; Jingdong Zhang; Ruonan Li; Mengyu Liu (Environmental Science and Pollution Research, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Fine mapping of the tiller inhibition gene TIN5 in Triticum urartu - Yaoqi Si; Qiao Lu; Shuiquan Tian; Jianqing Niu; Man Cui; Xiaolin Liu; Qiang Gao; Xiaoli Shi; Hong-Qing Ling; Shusong Zheng (Theoretical and Applied Genetics, 2022)

Bibliometric Review of Biodiversity Offsetting During 1992–2019 - Shuling Yu; Baoshan Cui; Chengjie Xie; Ying Man; Jing Fu (Chinese Geographical Science, 2022)

Synthesis and biological activity of amide derivatives derived from natural product Waltherione F - Hongbin Fang; Zhanfang Chen; Xuewen Hua; Wenrui Liu; Chenmeng Xue; Yi Liu; Xiaohe Zhu; Man Yuan; Shuang Cheng; Bingxiang Wang; Jing Ru; Dzmitry Bazhanau; et al. (Medicinal Chemistry Research, 2022)

Characteristics and formation mechanism of siltstone-mudstone rhythmic sedimentary sections in the Lower Silurian Longmaxi Formation in the Changning area, South Sichuan Basin, southwest China - Gaoxiang Wang; Lei Chen; Yang Yang; Cui Jing; Man Chen; Xiucheng Tan; Xin Chen; Di Cao; Zibo Wei; Minglong Li; Dong Huang (Frontiers of Earth Science, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Species and geographic specificity between endophytic fungi and host supported by parasitic Cynomorium songaricum and its host Nitraria tangutorum distributed in desert - Shuang-Man Miao; Yan-Yan Zhang; Jin-Long Cui; Gang Zhang (Archives of Microbiology, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Differential relationship of fungal endophytic communities and metabolic profiling in the stems and roots of Ephedra sinica based on metagenomics and metabolomics - Qi Zhang; Xiao-Zan Xue; Shuang-Man Miao; Jin-Long Cui; Xue-Mei Qin (Symbiosis, 2020)

Study on mechanical and permeability characteristics of nickel-copper-contaminated soil solidified by CFG - Qiang Wang; Man Li; Jingdong Yang; Jinyang Cui; Wenjun Zhou; Xiaoliang Guo (Environmental Science and Pollution Research, 2020)

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

Component analysis and antiasthmatic effects of Huashanshen dripping pill - Shuli Man; Nina Cui; Xuanshuo Liu; Long Ma; Changxiao Liu; Wenyuan Gao (Medicinal Chemistry Research, 2020)

QTL analysis and candidate gene identification for plant height in cotton based on an interspecific backcross inbred line population of Gossypium hirsutum × Gossypium barbadense - Jianjiang Ma; Wenfeng Pei; Qifeng Ma; Yanhui Geng; Guoyuan Liu; Ji Liu; Yupeng Cui; Xia Zhang; Man Wu; Xingli Li; Dan Li; XinShan Zang; et al. (Theoretical and Applied Genetics, 2019)

Design, synthesis, bioactivity, and DFT calculation of 2-thiazolyl-hydrazone derivatives as influenza neuraminidase inhibitors - Man-Ying Cui; Jian-Xia Nie; Zhong-Zhong Yan; Meng-Wu Xiao; Ding Lin; Jiao Ye; Ai-Xi Hu (Medicinal Chemistry Research, 2019)

Ecological Offsetting in China’s Coastal Wetlands: Existing Challenges and Strategies for Future Improvement - Shuling Yu; Baoshan Cui; Chengjie Xie; Xu Ma; Ying Man; Zhonghua Ning (Chinese Geographical Science, 2019)

Climate change mitigation in the coal mining industry: low-carbon pathways and mine safety indicators - Bing Wang; Chao-Qun Cui; Yi-Xin Zhao; Man Chen; Xiao-Chen Yuan (Natural Hazards, 2019)

Soil organic carbon in particle-size fractions under three grassland types in Inner Mongolia, China - Zijuan Xu; Zichuan Li; Hongyan Liu; Xiaodong Zhang; Qian Hao; Yang Cui; Shilei Yang; Man Liu; Hailong Wang; Gerty Gielen; Zhaoliang Song (Journal of Soils and Sediments, 2018)

mPGES-1-derived prostaglandin E2 stimulates Stat3 to promote podocyte apoptosis - Jing Yu; Yimei Wu; Lu Wang; Wen Zhang; Man Xu; Jiayu Song; Yu Fu; Yiyun Cui; Wei Gong; Shuzhen Li; Weiwei Xia; Songming Huang; et al. (Apoptosis, 2017)

Two new sesquiterpene glycosides isolated from the fresh needles of Pinus massoniana Lamb. - Yun-Chuan Xiao; Liang Ye; Man-Xi Zhao; Cui-Qi Yan; Wei Wang; Quan-Shu Huang; Kai Liang; Bao-Hua Meng; Xiao Ke (Natural Product Research, 2017)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

OsMSR15 encoding a rice C2H2-type zinc finger protein confers enhanced drought tolerance in transgenic Arabidopsis - Xin Zhang; Bin Zhang; Ming Juan Li; Xu Ming Yin; Li Fang Huang; Yan Chun Cui; Man Ling Wang; Xinjie Xia (Journal of Plant Biology, 2016)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Marinobacter shengliensis sp. nov., a moderately halophilic bacterium isolated from oil-contaminated saline soil - Yi-Jing Luo; Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Ya-Nan Wang; Heng-Lin Cui; Hua Cai; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

Quinoxaline-2,3-diones: potential d-amino acid oxidase (DAAO) inhibitors - Dongsheng Xie; Yanchao Wang; Jin Xie; Jun Lu; Junjun Cui; Man Zhang; Lei Fu; Yongxiang Wang (Medicinal Chemistry Research, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

The Novel Tetramethylpyrazine Bis-nitrone (TN-2) Protects Against MPTP/MPP+-Induced Neurotoxicity via Inhibition of Mitochondrial-Dependent Apoptosis - Daping Xu; Hongwei Duan; Zaijun Zhang; Wei Cui; Liang Wang; Yewei Sun; Ming Lang; Pui Man Hoi; Yifan Han; Yuqiang Wang; Simon MingYuen Lee (Journal of Neuroimmune Pharmacology, 2014)

Debris flows introduced in landslide deposits under rainfall conditions: The case of Wenjiagou gully - Jia-wen Zhou; Peng Cui; Xing-guo Yang; Zhi-man Su; Xiao-jun Guo (Journal of Mountain Science, 2013)

A novel rice calmodulin-like gene, OsMSR2, enhances drought and salt tolerance and increases ABA sensitivity in Arabidopsis - Guo-Yun Xu; Pedro S. C. F. Rocha; Man-Ling Wang; Meng-Liang Xu; Yan-Chun Cui; Luo-Ye Li; Yu-Xing Zhu; Xinjie Xia (Planta, 2011)